2015
DOI: 10.3747/pdi.2013.00290
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Examining the Effects of Tolvaptan on Residual Renal Function in Peritoneal Dialysis for Diabetics

Abstract: ♦ Background: For patients with end-stage renal disease (ESRD), peritoneal dialysis (PD) serves as a possible renal replacement therapy. However, most PD patients, particularly those with ESRD and diabetes mellitus, reportedly discontinue PD early, resulting in shorter survival periods and poorer prognosis because of overhydration. Recently, the vasopressin-2 receptor antagonist tolvaptan was approved for volume control in patients with heart failure. The present study aimed to identify the effects of tolvapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Serum albumin and UPCR did not affect the efficacy of TLV, contrary to previous results using furosemide [19]. The efficacy of TLV as a diuretic may be even higher given its success in patients undergoing peritoneal dialysis [29,30] and hemodialysis [31]. However, using thiazide diuretics with TLV attenuated TLV's diuretic effects of increasing UV and decreasing UOsm and BW.…”
Section: Discussioncontrasting
confidence: 55%
“…Serum albumin and UPCR did not affect the efficacy of TLV, contrary to previous results using furosemide [19]. The efficacy of TLV as a diuretic may be even higher given its success in patients undergoing peritoneal dialysis [29,30] and hemodialysis [31]. However, using thiazide diuretics with TLV attenuated TLV's diuretic effects of increasing UV and decreasing UOsm and BW.…”
Section: Discussioncontrasting
confidence: 55%
“…In a pilot study, a total of 24 patients after PD initiation were divided into two groups: those who received tolvaptan treatment and those who did not. As a result, the urine volume, renal Kt/V, and renal creatinine clearance levels were consistently decreased in the control group, whereas these parameters were maintained in the tolvaptan group at 6 and 12 months [132] .…”
Section: Volume Status and Diureticsmentioning
confidence: 91%
“…In addition, tolvaptan has recently become clinically available for the treatment of autosomal dominant polycystic kidney disease (ADPKD) in Japan, the European Union, the USA and other countries [ 11–13 ]. A pilot study revealed that tolvaptan increased urine volume in patients with kidney failure on peritoneal dialysis [ 14 ]; however, the efficacy of tolvaptan in HD patients remains to be investigated and it is not yet approved for use in kidney failure.…”
Section: Introductionmentioning
confidence: 99%